Perkelahian dalam Dunia Game (Fenomena Toxic pada Game Valorant) - Maziatul Putri; Damaiyanti, Varinia Pura (Program Studi Sosiologi, FISIP ULM, 2026)
In social life, humans are inextricably linked to conflict. This research was conducted in a community that includes Valorant players. The researchers aimed to understand the conflicts that occur among Valorant players and examine the impact of friendships after a conflict, using conflict theory by Ralf Dahrendorf and Lewis A. Coser. This study used a qualitative approach, with a phenomenological approach. Data collection was conducted through observation, interviews, and documentation. The results revealed disappointment among players when things don't go as expected. Superordination and subordination within Valorant also occurred, leading to perpetrators and victims of toxic behavior. Most of these relationships between perpetrators and victims ultimately resulted in strained relationships due to toxic behavior.